A Measurement Model of Information Sharing in E-Government Services: A Case Study of Kedah, Malaysia - Ahmad, Mazida; Omar, Mazni; Yasin, Azman; Ibrahim, Huda; Othman, Abdul Rahim (2018)
In order to provide a better delivery of e-government services, guides should be given to support information sharing and integration.Good practices in information sharing among state government agencies should be adopted. In present Malaysia, there is insufficient information regarding the current practices, states or levels of maturity, requirements, and models adopted in relation to information sharing for the eservices’ implementation among government agencies.Previous studies in Malaysia have been conducted in relation to critical factors for e-government services and information sharing.These previous studies focused on a conceptual framework that requires more efforts in creating an integrative model to guide information sharing for egovernment services. The main aim of this study is to propose a measurement model of information sharing model to support the implementation of e government services for Malaysian and Indonesian environments.A set of questionnaire has been distributed to a sample of private sectors that are using e-government services or e-procurement in conducting their purchasing process.The analysis of the data was carried out using Structural Equation Modeling (SEM) and Partial Least Square (PLS) techniques to examine the relationships between the identified factors which were grounded on the D&M IS Success Model. The outputs are also expected to formulate guidelines and procedures to best guide the information sharing framework to support the implementation of e-government services in Malaysia and Indonesia.